Relationship Between Technological Resources and Meaningful Learning in Secondary Students - Bonilla-Guachamín, Johanna (2021)
Technological resources have as a goal to facilitate knowledge acquisition, storage, and use, to achieve the results proposed in the teaching-learning process and to obtain meaningful learning. The research proposed as following is based on a correlational methodology, which is oriented towards the improvement of the teaching-learning process and has as aim, to study the relationship between technological resources and meaningful learning of students belonging to high-school level. Results obtained are as following: (a) higher availability of technological resources produce an increase of knowledge acquisition (r = 0.42, p =< 0.001) and (b) while there is higher scientific literature available, students’ skills will be higher too (r = 0.53, p =< 0.001)